Intensification of Systemic Therapy in Addition to Definitive Local Treatment in Nonmetastatic Unfavourable Prostate Cancer: A Systematic Review and Meta-analysis - Rajwa, Pawel; Pradere, Benjamin; Gandaglia, Giorgio; van den Bergh, Roderick C N; Tsaur, Igor; Shim, Sung Ryul; Yanagisawa, Takafumi; Laukhtina, Ekaterina; Mori, Keiichiro; Mostafaei, Hadi; Quhal, Fahad; Bryniarski, Piotr; et al. (European urology, 2022)
CONTEXT: Several recent randomised trials have evaluated the role of combination systemic treatment using androgen deprivation therapy (ADT) plus chemotherapy or an androgen receptor signaling inhibitor (ARSI) in patients with high-risk and/or unfavourable nonmetastatic prostate cancer (nmPC). OBJECTIVE: To assess the outcomes associated with adding combination systemic treatment to primary definitive local therapy in patients with high-risk and/or unfavourable nmPC. EVIDENCE ACQUISITION: We queried the PubMed, Web of Science, and Scopus databases and conference abstracts to identify prospective randomised trials examining the value of adding chemotherapy or an ARSI to ADT and primary local therapy with curative intent for nmPC. The primary endpoints were overall survival (OS), cancer-specific survival (CSS), metastasis-free survival (MFS), and failure-free survival (FFS). Secondary endpoints included adverse events (AEs) and pathologic outcomes. EVIDENCE SYNTHESIS: We identified 15 randomised studies, of which nine evaluated chemohormonal and six investigated ARSI-based treatment strategies. In both radical prostatectomy (RP) and radiation therapy (RT) settings, addition of docetaxel to ADT was associated with significantly better CSS (pooled hazard ratio [HR] 0.68, 95% confidence interval [CI] 0.49-0.95; p = 0.025), MFS (pooled HR 0.82, 95% CI 0.71-0.95; p = 0.008), and FFS (pooled HR 0.70, 95% CI 0.62-0.79; p < 0.001); the difference did not meet the conventional level of statistical significance for OS (pooled HR 0.86, 95% CI 0.73-1.01; p = 0.072). For patients treated with RT alone, docetaxel-based combination treatment did not meet the significance threshold set for OS (p = 0.3), CSS (p = 0.072), or MFS (p = 0.079), but the difference for FFS was statistically significant (pooled HR 0.72, 95% CI 0.63-0.84; p < 0.001). On network meta-analyses including RT studies, ARSI + ADT outperformed docetaxel + ADT for survival endpoints and had a more favourable AE profile. CONCLUSIONS: Intensification of systemic therapy with docetaxel or an ARSI in addition to ADT improves oncologic endpoints in high-risk and/or unfavourable nmPC treated with local definitive therapy. The highest efficacy was achieved with ARSI + ADT, specifically in patients treated with RT. PATIENT SUMMARY: Our findings highlight that selected patients with high-risk nonmetastatic prostate cancer benefit from intensification of systemic therapy beyond hormonal treatment.
Keywords: Humans; protinádorové látky; prospektivní studie; Antineoplastic Agents; protokoly protinádorové kombinované chemoterapie; Antineoplastic Combined Chemotherapy Protocols; Docetaxel; Prostatic Neoplasms; Androgen Antagonists; docetaxel; antagonisté androgenů; mužské pohlaví; nádory prostaty; Male; lidé; Prospective Studies